2019
DOI: 10.1016/j.isci.2019.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cells Sense Fibers by Coiling on them in a Curvature-Dependent Manner

Abstract: SummaryMetastatic cancer cells sense the complex and heterogeneous fibrous extracellular matrix (ECM) by formation of protrusions, and our knowledge of how cells physically recognize these fibers remains in its infancy. Here, using suspended ECM-mimicking isodiameter fibers ranging from 135 to 1,000 nm, we show that metastatic breast cancer cells sense fiber diameters differentially by coiling (wrapping-around) on them in a curvature-dependent manner, whereas non-tumorigenic cells exhibit diminished coiling. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

7
3

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 52 publications
4
28
0
Order By: Relevance
“…Overall, the utility of lateral protrusions remains poorly understood, as classic 2D culturing methods limit the formation of lateral protrusions, while 3D gels lack the homogeneity and topographic patterning needed to study the role of fiber geometry on protrusion frequency, morphology, and dynamics. To partially remedy this, we recently used orthogonal arrangement of fibers of mismatched fiber diameters to constrain cell migration along large diameter fibers while studying lateral protrusions of various shapes and sizes on smaller diameter fibers 30,31 . We observed the protrusions formed in an integrin-dependent manner on small diameter fibers, and notably suspended flat ribbons of equivalent widths did not capture protrusive sensitivity to curvature 30 .…”
mentioning
confidence: 99%
“…Overall, the utility of lateral protrusions remains poorly understood, as classic 2D culturing methods limit the formation of lateral protrusions, while 3D gels lack the homogeneity and topographic patterning needed to study the role of fiber geometry on protrusion frequency, morphology, and dynamics. To partially remedy this, we recently used orthogonal arrangement of fibers of mismatched fiber diameters to constrain cell migration along large diameter fibers while studying lateral protrusions of various shapes and sizes on smaller diameter fibers 30,31 . We observed the protrusions formed in an integrin-dependent manner on small diameter fibers, and notably suspended flat ribbons of equivalent widths did not capture protrusive sensitivity to curvature 30 .…”
mentioning
confidence: 99%
“…Both 2D substrates and micropatterned stripes provide controllable and reproducible environments, but neither fully models the details of in vivo native cellular environments, which consist of extracellular matrices of fibrous proteins, with these fibers having different radii. Our earlier in vitro recapitulation of the effects of fiber curvature showed that both protrusive and migratory behavior is sensitive to fiber diameter [19][20][21] . Furthermore, we have shown that suspended flat 2D ribbons do not capture the protrusive behavior observed on suspended round fibers 19 , thus, we wanted to inquire if the CIL rules developed on 1D collision and 2D assays extend to contextually relevant fibrous environments.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by the Yamada group have demonstrated how single-cell behavior in 3D microenvironments can be recapitulated through the use of narrow 1D microprinted lines of varying widths (1-40 µm) [32] . Microprinted lines are essentially 2D surfaces, and in our study, we inquired if suspended 1D fibrillar architecture of precisely controlled fiber diameters (150-6000 nm) and interfiber spacing regulated nuclear responses of uniaxial spread cells, as we have previously shown protrusive, contractile, and migratory behavior of uniaxial cells to be sensitive to fiber curvature and spacing [33][34][35][36][37][38][39] . In this study, we chose nucleus rupture and the spatial localization of YAP/TAZ as two markers of nuclear response to changes in fiber curvatures.…”
Section: Introductionmentioning
confidence: 99%